Religiosity in Tere Liye’s Janji novel (an Approach to the Sociology of Literature) - Chamalah, Evi; Nuryyati, Reni (Universitas Ahmad Dahlan, 2023)
Novel Janji is one the novels that tell the story of the journey of a religious school child who is looking for a former religious school student decades ago. The author describes religious school children being able to search for someone who disappeared decades ago according to their teacher’s instructions. This study uses a literary sociological analysis approach. The results of the study show that the story in the novel Janji contains five dimensions of religiosity, namely the dimension of belief, the dimension of ritual, the dimension of experience, the dimension of knowledge, and the consequential dimension. In the dimension of belief, it can be seen in the character's belief in doing good, not committing acts of corruption, and the belief in using money to worship. In the ritual dimension, religiosity is seen in the implementation of the five daily prayers, ablution before prayer, Friday prayers, daily expressions, and Idul Fitri prayers. In addition, in the dimension of experience, religiosity is seen in the character's experience of doing bad things, the experience of the character studying at a religious school, and the experience of the character eating inappropriate food for five years. In the knowledge dimension, the value of religiosity can be seen in the concept of sin, the concept of halal and haram, the obligation to pray five times a day, treasures as entrusted in the world, and stories of prophets in the past. At the end, the consequential dimension appears in the actions of the characters in the present which are based on the experiences of the characters in the past.